X‐ray spectral characteristics of typical clays in China and their application in clay classification. (27th February 2023) - Zhai, Juan; Lai, Wanchang; Lin, Hongjian; Li, Dan; Shi, Jie; Wang, Guangxi; Yang, Qiang; Liu, Guanhua
Abstract: The variety and content of minerals in clay determine its quality and use. The x‐ray fluorescence characteristics of seven elements, that is, Mg, Al, Si, K, Ca, Ti, and Fe, in clay samples were studied using the energy‐dispersive x‐ray fluorescence (EDXRF) method. The application of wavelet transform was used to analyze the overlapping peaks of the FeKα and MnKβ and the CaKα and KKβ spectral lines and to measure the spectral peak count rate and the content of seven elements. The weight of classified elements in clay was calculated through principal component analysis, and the clay samples from four clay‐producing areas were classified using the K‐means clustering method. The results showed that the accuracy of classification using the count rate of seven elements reached 97.73%. The average accuracy of the classification results of the content of seven elements reached 80.68%. A comparison of the results showed that the EDXRF spectral peak information provides a reliable scientific method for the identification and tracing of clay and its products. In addition, tracing the origin of clay and its products can also indirectly assess the radiation level and its impact on the radiation environment based on the radiation index test results.